2020
DOI: 10.1007/s10653-020-00655-7
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical model of the spatial distribution of arsenic in groundwaters in Gujarat State, India

Abstract: Geogenic arsenic contamination in groundwaters poses a severe health risk to hundreds of millions of people globally. Notwithstanding the particular risks to exposed populations in the Indian sub-continent, at the time of writing, there was a paucity of geostatistically based models of the spatial distribution of groundwater hazard in India. In this study, we used logistic regression models of secondary groundwater arsenic data with research-informed secondary soil, climate and topographic variables as princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
0
25
0
Order By: Relevance
“…The area under the ROC (receiver operator characteristic) curve (AUC) is 0.86, which in general can range between 0.5 (random model) and 1 (perfect model) and represents how well a binary model can predict both low and high values as assessed over numerous probability cutoff values [ 65 ]. The AUC of this model is generally a better result than that of similar regional or country-scale groundwater quality studies (where reported), for example, 0.84 for fluoride in India [ 66 ], 0.71–0.83 for arsenic in Gujarat [ 14 ], 0.82 for arsenic in the USA [ 67 ], 0.80 for arsenic in Pakistan [ 6 ], or 0.74 for arsenic in Uttar Pradesh [ 15 ]. The overall accuracy of the model as applied to the test dataset of 0.79 is significantly higher than the no information rate of 0.58 ( p value < 2.2 × 10 −16 ) and is comparable to the average accuracy with OOB samples of 0.77.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The area under the ROC (receiver operator characteristic) curve (AUC) is 0.86, which in general can range between 0.5 (random model) and 1 (perfect model) and represents how well a binary model can predict both low and high values as assessed over numerous probability cutoff values [ 65 ]. The AUC of this model is generally a better result than that of similar regional or country-scale groundwater quality studies (where reported), for example, 0.84 for fluoride in India [ 66 ], 0.71–0.83 for arsenic in Gujarat [ 14 ], 0.82 for arsenic in the USA [ 67 ], 0.80 for arsenic in Pakistan [ 6 ], or 0.74 for arsenic in Uttar Pradesh [ 15 ]. The overall accuracy of the model as applied to the test dataset of 0.79 is significantly higher than the no information rate of 0.58 ( p value < 2.2 × 10 −16 ) and is comparable to the average accuracy with OOB samples of 0.77.…”
Section: Resultsmentioning
confidence: 95%
“…The prediction model ( Figure 2 a) captures known arsenic-prone areas in the alluvial sediments along the Ganges and Brahmaputra plains [ 27 ] and in Gujarat [ 14 ] and Punjab [ 43 ]. It also identifies less well-known or previously undocumented areas such as Haryana, Jammu and Kashmir, and central Madhya Pradesh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other processes, including complexation of arsenic by dissolved humic substances, competitive desorption, oxidation of sulfide minerals, geothermal activities, and mining-related activities, may also influence arsenic concentrations in groundwaters [18,19]. Spatial geostatistical models of the distribution of groundwater arsenic have been produced at both state (Gujarat [20], Uttar Pradesh [21]) and national scales [22,23] to help better fully understand the distribution of groundwater arsenic hazard in India, particularly given the lack of all-India systematic groundwater arsenic testing. Podgorski et al [22] generated a random forest model with over a hundred thousand arsenic concentration observations and over two dozen environmental parameter predictors to identify high groundwater arsenic (>10 µg/L) in well-known arsenic-contaminated areas in the alluvial sediments along the Ganges and Brahmaputra plains and in Gujarat and Punjab states and to capture less-known or previously unrecorded areas.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to estimate the magnitude of groundwater arsenic-attributable cardiovascular disease (CVD) mortality in India. These aims were achieved by (i) generating machine learning models of the probability distribution of groundwater arsenic concentrations exceeding four different thresholds (10,20,50, 80 µg/L); (ii) thereby creating a pseudo-contour map of groundwater arsenic concentrations; (iii) estimating the state/district-level population exposed to these four arsenic concentration ranges (10-20, 20-50, 50-80, >80 µg/L) based on simple exposure models; (iv) determining the state/district-level population-attributable fraction (PAF) of CVD mortality attributable to exposure to groundwater arsenic; and hence (v) determining the state-level CVD mortality attributable to groundwater arsenic. Lastly, (vi) the costs of arsenic-attributable CVD mortality were estimated for the whole of country.…”
Section: Introductionmentioning
confidence: 99%